FOSTERING JAPANESE STUDENTS’ LOGICAL THINKING TO FORMULATE A COMMON UNDERSTANDING OF LOGICS BETWEEN TEACHERS AND STUDENTS - Masumi, Atsushi (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Japan’s MEXT’s (The Ministry of Education, Culture, Sports and Technology) survey in 2016 shows that Japanese high school students have difficulty writing their opinions logically in English. To foster students’ logical thinking in class, it is necessary to formulate a common understanding regarding logic between teachers and students. However, the image of logic is not always shared well among teachers, students, and between teachers and students in an L2 class. Very little is also known about the effective methods to share a common understanding of logic. The aim of this study is to explore a possible method. The experiment was conducted with 105 high school students (three groups with 35 members each) and 11 English teachers. Each group (L1 essay analysis, L2 essay analysis, and L1 and L2 essay analyses) received lessons on essay analysis (twice a week for 2–3 weeks) using task sheets which were purposefully developed. Before and after the experiment, teachers and students were asked to write their definition of logics and English writing tests were conducted for students. The results of the statistical analysis (a quantitative textual analysis, t-test and effect size analysis) shows that 1) a consensus on logics is necessary among teachers before instructing essay writing, 2) the instruction using L1 essay contributes to eliminating the difference in the perception of logics between teachers and students, and 3) it enhances students’ logics in English essay writing. This study contributes well to progressing to the next step which supports students to write essays logically.